2023
DOI: 10.1111/mec.16998
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide variant analyses reveal new patterns of admixture and population structure in Australian dingoes

Abstract: Hybridisation between two populations or species leads to genetic admixture, which alters the genetic identity of the species or population and can result in a new hybrid species. In some cases, genetic dilution can lead to extinction of the species or populations involved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 126 publications
2
9
0
Order By: Relevance
“…Erroneous reports of hybridization from microsatellites have been found in a wide range of organisms including newts (Miralles et al., 2023), lemurs (Poelstra et al., 2022), dingoes (Cairns et al., 2023), polecats (Szatmári et al., 2021) and Cape hakes (Henriques et al., 2016). These false reports of hybridization were mainly attributed to the lack of power resulting from the use of a (very) small number of hyper‐variable loci.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erroneous reports of hybridization from microsatellites have been found in a wide range of organisms including newts (Miralles et al., 2023), lemurs (Poelstra et al., 2022), dingoes (Cairns et al., 2023), polecats (Szatmári et al., 2021) and Cape hakes (Henriques et al., 2016). These false reports of hybridization were mainly attributed to the lack of power resulting from the use of a (very) small number of hyper‐variable loci.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the high risk of homoplasy (Chambers & MacAvoy, 2000; Henriques et al., 2016), the frequent occurrence of null alleles (Dakin & Avise, 2004), high mutation rate and difficulties scoring alleles (Pompanon et al., 2005; Selkoe & Toonen, 2006), are well‐documented issues inherent to the nature of microsatellites, but are often ignored, potentially leading to false reports of hybridization (e.g. Cairns et al., 2023; Poelstra et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization with domestic dogs was previously highlighted as a main concern for dingo conservation, since high levels of hybridization were observed in dingoes from southeastern Australia (Newsome and Corbett 1985; Jones 1990; Corbett 2001; Wilton 2001; Elledge et al 2008; Stephens et al 2015; Cairns et al 2020; Cairns 2021; Cairns et al 2021). However, a recently published study using genome-wide SNP data has shown these occurrences are less common than previously thought (Cairns et al 2023). Policy and legislation in Australia currently employs the term “wild dog” to refer to dingoes, feral domestic dogs and dingo-dog hybrids, assuming that pure dingoes are virtually extinct in the wild and that dingo-dog hybrids are common (Fleming 2001; DEPI 2013; Bird and Bowman 2016; NWDAP 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Although dingoes are present across different bioregions in Australia, at least two distinct mainland dingo lineages have been identified, one in the northwest and one in the southeast, alongside one offshore lineage on K’gari (formerly known as Fraser Island) (Cairns and Wilton 2016; Cairns et al 2017; Cairns et al 2018; Greig et al 2018; Zhang et al 2020). Genome-wide SNP data suggest there may be additional biogeographic structure in the mainland dingo population (Cairns et al 2023). As the apex terrestrial predator since the extinction of the thylacine, dingoes play an important role in maintaining the ecosystems of Australia (Glen et al 2007; Johnson et al 2007; Letnic et al 2009; Wallach et al 2010; Letnic et al 2011; Letnic et al 2012).…”
Section: Introductionmentioning
confidence: 99%